A Study to Assess the Quality of Life of Under Graduate B.sc. Nursing Students of Dinsha Patel College of Nursing, Nadiad (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Aims: Quality of life (QOL) is a subjective concept because the interpretation of eachindividual depends on his/her personal point of view. It is also multidimensional, given the influence offactors related to education, economy and socio-cultural aspects.Although the quality of life (QOL) of nursing students is a relatively well-researched topic in the West, thereis a lack of it in developing countries like India. The aim of this study was to examine the QOL of Indianundergraduate nursing students and its associations with socio demographic and other parameters.Methods: This cross-sectional study was conducted in nursing college in Gujarat, India. In this institutionundergraduate nursing students were selected. Usually, students start nursing program at 18 years of age.During the course of their study they learn different medical and paramedical related nursing subjects.Also, from the first year, they have their first direct clinical contact with patients in hospitals (scheduledclinical rotations). All the eligible subjects were approached after class hours to participate in the survey.Participation was completely voluntary. Informed consent was obtained from all individual participantsincluded in the study. The questionnaires were anonymous, personally identifiable information such as nameand identification number was not collected. Students were requested to sit at a fair distance from each otherso as to assuage their privacy concerns. Students were assured of confidentiality and informed that the datacollected shall be published and later would be provided to nursing education policymakers. The studywas approved by the Institutional Ethics Committee and was conducted according to the ethical principleslaid down by the declaration of ICMR. A cross-sectional study was conducted on 225 nursing students inNadiad Gujarat, India. Students self-reported their QOL using the World Health Organization Quality ofLife-BREF (WHOQOL-BREF).Data were collected on the individuals’ characteristics, including the yearof study, substance use, physical exercise, academic performance, and other parameters.Results & Conclusion: The present study evaluates the quality of life of B.Sc nursing students of DinshaPatel College of Nursing. On the basis of the findings the researchers concluded that the 146 students areperceived that they are live with average Quality of Life.
Keywords: QOL: Quality of life, SF: Self-efficacy, SOC: Students Sense of coherence, LOO: Level of optimism, HPL: Health promoting lifestyle, QCL: Quality of college life.